Analysis of Fish Farmers’ Satisfaction In Banjarbaru City With The Tilapia Fish (Oreochromis niloticus) Seed Assistance Program of The Mandiangin Freshwater Aquaculture Center Using The Servqual Approach - Ermayani; Emmy Sri Mahreda; Leila Ariyani Sofia (International Journal of Science and Environment (IJSE), 2026)
The Tilapia fish seed assistance program implemented by the Mandiangin Freshwater Aquaculture Center (BPBAT Mandiangin) for fish farmer groups in Banjarbaru City is one form of government support for the development of aquaculture enterprises. This study aimed to analyze fish farmers’ satisfaction with the BPBAT Mandiangin Tilapia fish seed assistance program using the SERVQUAL approach. The study was conducted in Banjarbaru City, South Kalimantan Province. Eleven respondents were purposively selected, consisting of seven fish farmer group leaders and four direct beneficiary farmers. The primary data collected were analyzed using the SERVQUAL approach, which comprises five service dimensions: tangibles, reliability, responsiveness, assurance, and empathy. The results showed that all service quality dimensions were classified as very good, with scores of 4.71 for Tangibles, 4.77 for Reliability, 4.80 for Responsiveness, 4.84 for Assurance, and 4.85 for Empathy. These findings indicate that the fish farmers were highly satisfied with the quality of services provided, including administration, timeliness, seed quality, staff competence, and assistance during program implementation.